Initiation of Virtual Court System during COVID-19 Pandemic and E-Judiciary: Challenges and Way Forward - Mohammad Ikbal Hasan; Badsha Mia (Daengku: Journal of Humanities and Social Sciences Innovation, 2021)
The Constitution of the people’s republic of the Bangladesh recognizes the right to protection of law and access to justice as fundamental rights. But the COVID-19 pandemic has, in effect, suspended the execution of these fundamental rights. The immediate impact of the pandemic has triggered courts across Bangladesh be shut to maintain social distancing. Third organ of the State cannot remain static during a crisis of this scale and duration. On this backdrop, the judiciary has started the operation of the virtual court system from May, 2020. Opening the doors to virtual courts, Bangladesh has joined a list of countries across the world where the justice system has similarly responded to the coronavirus-induced lockdown with increased digitalization. If the e-judiciary is introduced properly, reduction of the delay in the court process and elimination of the backlog of cases, which are the biggest challenge for the judiciary in our country, can be resolved rapidly. The virtual court would play a pioneering role in establishing e-judiciary. The Supreme Court of Bangladesh has taken an extraordinary test with the limited resources and digital infrastructures for carrying out virtual courts during this Covid-19 pandemic. The core objective of this study is to investigate the challenges of virtual court system in delivery of justice during COVID 19 pandemic situation and identify the way out to make the digital judiciary as permanent system for effective delivery of E-justice. The success of this noble initiative would largely depend upon ensuring technological support and legal requirements for e-courts and framing and implementing sound national policy and action plan for e-judiciary.